Civil Servant in the System of the Subjects of Administrative Law - Vyacheslav Vladimirovich Kizilov (Сибирское юридическое обозрение, 2011)
Drawing on a critical analysis of the classifications of the subjects of law in the legal sciences: theory of State and law, administrative law, the article determines a civil agent's status in the system of administrative law. Dualism of active legal capacity and legal capacity of a civil agent is discussed. The author provides principles of distinguishing public authority representatives from civil service officials.